Holistic Approaches in the Development of Reading in teaching the Macedonian Language - Tomevska Ilievska, Elizabeta (Faculty of Physical Education, Sport and Health, Skopje, 2020)
Reading, as a language process, has a basic meaning in relation to the overall learning and progress of students. This is a complex and long-lasting process that in educational conditions, in its most elementary form, takes place within the first educational cycle in primary education. Contrary to traditional understandings, modern concepts of language literacy are being developed today, which are increasingly treated as a holistic process of individual skills that form the basis of language. The main goal of this concept is "learning everything" "through everything" through the use of various activities interwoven with elements of play and informality. One of the basic principles of this concept is the development (of the cognitive, emotional and social components), the gradualness and individualization at the beginning of the language literacy process, then during the process itself, by monitoring the progress and micro method modeling, adapted to individual needs and at the end of the process of language literacy, when everyone is expected to achieve their own maximum in development, to the point of building an individual reading strategy. These are serious and complex requirements and priorities that are adopted on a theoretical level (by at least a part of the teachers) and that are occasionally implemented in everyday teaching practice. This raises the question of ways of educational compensation in order for modern strategies to become a daily teaching routine. The alternation of the "entrance" in the development of this process is possible through the implementation of the concept of global reading also in the Macedonian language. Due to its structure and use of a modern method for initial language literacy, global reading partially deviates from the previous conventional forms, but is not in collision with the nature of the Macedonian language.
Keywords: global reading, language literacy, language skills, reading patterns (conventional and alternative).